If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6(x-2)=15
We move all terms to the left:
3x+6(x-2)-(15)=0
We multiply parentheses
3x+6x-12-15=0
We add all the numbers together, and all the variables
9x-27=0
We move all terms containing x to the left, all other terms to the right
9x=27
x=27/9
x=3
| /c=18 | | 3x+6(x-2)=17 | | `1-8n=33 | | 3+7b=38 | | 7x-52/4=17x | | 0.25(x+12)=30 | | 0.75x=1.3 | | 3x+-8=26 | | -7x+2=-4x+7 | | 5 | | 32=–3x–1 | | b4+ –9=–13 | | 13+3v=-20 | | –a+104=0 | | 21=3(v+8) | | 5x–9=5x+19 | | 13+3v=-0 | | 7x-3=2x+7 | | |y=-1 | | 3/4(y+1)=-6 | | 16.67x-1=0 | | 3/2(x-1/3)-x+1/3(3x-6)=3/2(x+1/3) | | 2x-7+5x+3+x=180 | | 3(4x+2)=5(3+3x) | | z+12=8 | | –2(v+12)=–12 | | -2x-2(-5x+13)=14 | | y÷4=2 | | 8r2+1=321 | | 7s+42=180 | | 114+7x+23=90 | | 10x-1=-125 |